The Athena project [compact disc, unabridged] : a thriller - Thor, Brad (Audioworks/Simon and Schuster Audio, 2010)
A group of female warriors from the nation's most elite counter-terrorism unit-- the United States Army's 1st Special Forces Operational Detachment Delta--deploys on a dangerous international assignment. Their code name: Athena Project.